External shocks and monetary policy under the inflation targeting regime (ITR): An analysis of the determinants of inflation for the period 2000-2021 - Araujo, Elisangela Luzia; de Araújo, Eliane; Ramalho Ribeiro da Fonseca, Mateus; Mourão, Paulo Reis (PSL Quarterly Review, 2023)
This article theoretically and empirically investigates the determinants of inflation in a sample of 83 countries, including countries that adopt an inflation targeting regime (ITR) and countries that do not, for the period 2000 to 2021. The hypothesis that guides the research is that the recent events or shocks in the global economy (the subprime crisis, the “Eurozone” crisis, the COVID-19 pandemic and, more recently, the war in Ukraine, among others) have resulted in supply shocks – exchange rates, food and energy – causing a rise in inflation and bringing recessive effects that may be more pronounced in ITR countries, given the greater institutional rigidity of the regime. The empirical part of the research includes an analysis of the determinants of inflation in the sample of ITR and non-ITR countries, with a focus on variables that represent supply shocks, in addition to a proxy for the existence of global conflicts, the latter being a potential contribution of the research. The main results, despite the differences between developed and developing economies, suggest that the commodity index, exchange rate variations, and global conflicts positively impacted inflation in the analyzed period.